EXPLORING THE IMPLEMENTATION OF ENGLISH TEACHER’S TEACHING STRATEGIES - Enung Nuraidah; Agus Sapto Nugroho; Novita Pri Andini (LEAD (Language, Education and Development), 2021)
This research-based article is anchored on the investigation of the implementation of English teacher’s teaching strategies. It was aimed to find out what teaching strategies that the teacher used and how they were implemented in the classroom. This qualitative study used a descriptive approach. The participant and the subject was an English teacher teaching grade 8 in senior high school in Purwokerto. The data were collected through observation, interview, and documentation. They were analyzed using a triangulation method. The results show that the English teacher used such strategies as indirect instruction, interactive study, and direct instruction in their teaching learning process. The implementation of direct instruction was rarely used. On the reverse, the realization of indirect instruction was quite frequently used in the form of problem-solving. Meanwhile, the actualization of interactive instruction strategy covered brainstorming, group work, and role-play. The conclusive finding suggests that the implementation of those teaching strategies create enjoyable and effective learning atmosphere and therefore facilitate to achieve favorable learning objectives.